Dark carbon fixation in stream carbon cycling - Machado‐Silva, Fausto; Bastviken, David; Miranda, Marcio; Peixoto, Roberta Bittencourt; Marotta, Humberto; Enrich‐Prast, Alex (Limnology and oceanography, 2024)
Headwater streams are often characterized by turbulence, organic matter inputs from terrestrial systems, net heterotrophy, and the microbial loop supplying carbon and energy for consumers. However, ecological models overlook dark carbon fixation (DCF), the light‐independent inorganic carbon uptake, mainly based on chemosynthesis, using energy yields from redox reactions. The quantification of microbial biomass production, including DCF, heterotrophic production (HP), gross primary production (GPP), and ecosystem respiration (ER) in lotic aquatic systems, has long yet to be addressed. Here, we investigate HP and DCF in water, sediment, and litter in addition to GPP and ER from streams in pristine rainforests in three distinct sub‐basins of the Amazon River, assessing the variety of turbid, black, and clear waters. We observed mean (min–max) values of microbial biomass production of about 0.1 (0.02–1.2), 3.2 (0.8–14.1), and 0.1 (0.02–0.5) mg C m−2 h−1 in water, sediment, and litter samples, in which DCF : HP showed mean (min–max) values of 0.5 (0.2–2), 0.02 (0.001–0.07), and 0.2 (0.001–0.5). Hence, measurements yielded DCF of similar magnitude as HP in water and litter but significantly lower in sediment, indicating that DCF supplied more carbon to planktonic and litter microbes than in top sediments of streams. Literature comparisons show similar DCF and GPP, both being lower than ER in streams. Finally, we found stream DCF higher than in lentic systems, suggesting that flow and turbulence may accelerate chemosynthesis.